Ethically inclined models of authorship and lyric subjectivity in the poetry of Adília Lopes - Stuart-Thompson, Andrzej (eLyra: Development, 2019)
Adília Lopes’ gender-conscious and other-orientated poetry expresses ethical concerns. The “inclined” and non-erect perspective of her lyric “I” (which accords with the concept of “inclination” coined by Italian feminist philosopher Adriana Cavarero), together with her experimentation with an “aesthetics of care” (akin to that proposed by eco-feminist scholar Josephine Donovan), engender texts which are sites of ethical encounters between author and reader. Meanwhile, her models of authorship and lyric subjectivity are imbued with transformative ethical implications, through their revelation (and redemption of) culturally suppressed and philosophically disparaged vulnerabilities that are common to both the human and the non-human conditions.